Head-to-head comparison between endoscopic ultrasound guided lumen apposing metal stent and plastic stents for the treatment of pancreatic fluid collections: A systematic review and meta-analysis - Guzmán-Calderón, Edson (2022)
Background/Aims: Peripancreatic fluid collections (PFCs) result from acute or chronic pancreatic inflammation that suffers a rupture of its ducts. Currently, there exists three options for drainage or debridement of pancreatic pseudocysts and walled-off necrosis (WON). The traditional procedure is drainage by placing double pigtail plastic stents (DPPS); lumen-apposing metal stent (LAMS) has a biflanged design with a wide lumen that avoids occlusion with necrotic tissue, which is more common with DPPS and reduces the possibility of migration. We performed a systematic review and meta-analyses head-to-head, including only studies that compare the two main techniques to drainage of PFCs: LAMS vs DPPS. Methods: We conducted a systematic review in different databases, such as PubMed, OVID, Medline, and Cochrane Databases. This meta-analysis considers studies published from 2014 to 2020, including only studies that compare the two main techniques to drainage of PFCs: LAMS vs DPPS. Results: Thirteen studies were included in the meta-analyses. Only one of all studies was a randomized controlled trial. These studies comprise 1584 patients; 68.2% were male, and 31.8% were female. Six hundred sixty-three patients (41.9%) were treated with LAMS, and 921 (58.1%) were treated with DPPS. Six studies included only WON in their analysis, two included only pancreatic pseudocysts, and five studies included both pancreatic pseudocysts and WON. The technical success was similar in patients treated with LAMS and DPPS (97.6% vs 97.5%, respectively, P =.986, RR = 1.00 [95% CI 0.93-1.08]). The clinical success was similar in both groups (LAMS: 90.1% vs DPPS: 84.2%, P =.139, RR = 1.063 [95% CI 0.98-1.15]). Patients treated with LAMS had a lower complication rate than the DPPS groups, with a significant statistical difference (LAMS: 16.0% vs DPPS: 20.2%, P =.009, RR = 0.746 [95% CI 0.60-0.93]). Bleeding was the most common complication in the LAMS group (33 patients, [5.0%]), whereas infection was the most common complication in the DPPS group (56 patients, [6.1%]). The LAMS migration rate was lower than in the DPPS (0.9% vs 2.2%, respectively, P =.05). The mortality rate was similar in both groups, 0.6% in the LAMS group (four patients) and 0.4% in the DPPS group (four patients; P =.640). Conclusion: The PFCs drainage is an indication when persistent symptoms or PFCs-related complications exist. EUS guided drainage with LAMS has similar technical and clinical success to DPPS drainage for the management of PFCs. The technical and clinical success rates are high in both groups. However, LAMS drainage has a lower adverse events rate than DPPS drainage. More randomized controlled trials are needed to confirm the real advantage of LAMS drainage over DPPS drainage.